Association of TRF2 expression and myeloid-derived suppressor cells infiltration with clinical outcome of patients with cutaneous melanoma. (1st January 2021) - Ilié, Marius; Lantéri, Elisabeth; Chamorey, Emmanuel; Thamphya, Brice; Hamila, Marame; Montaudié, Henri; Picard-Gauci, Alexandra; Gardrat, Sophie; Passeron, Thierry; Lassalle, Sandra; Long-Mira, Elodie; Cherfils-Vicini, Julien; et al.
ABSTRACT: The outcome of patients with cutaneous melanoma has been strongly modified by recent advances obtained with Immune Checkpoint Inhibitors (ICIs). However, despite this breakthrough, durable response to ICIs is limited to a subset of patients. We investigated whether the expression of TRF2, which preserves telomere integrity, and have an effect on tumor immunosurveillance notably by directly recruiting and activating myeloid-derived suppressor cells (MDSCs), could be a prognostic biomarker in patients with relapsed or metastatic melanoma based on different treatment regimens. We evaluated retrospectively the association of TRF2 expressed in melanoma cells in combination with intratumoral CD33+ CD15+ CD14- MDSCs, as detected by immunohistochemistry and quantified by digital analysis, to clinicopathological features and overall survival (OS) among 48 patients treated with ICIs and 77 patients treated with other treatment options. The densities/mm 2 of TRF2+ cells ( P =.003) and CD33+ cells ( P =.004) were individually significantly related to poor OS. In addition, only the combined expression of CD33+/CD15+/CD14- cells/mm 2 was significantly correlated to poor OS ( P =.017) in the whole study population as well as in patients treated by ICIs ( P =.023). There was no significant difference in OS when analyzing the other markers individually or in combination according to the treatment regimen. The pre-treatment assessment of TRF2 expression and CD33+ cells/mm 2 along with the density of CD33+/CD15+/CD14- cells/mm 2 could assess OS and better predict clinical response of patients with melanoma treated by ICIs.